2023
DOI: 10.3390/catal13071083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photocatalyst on Rheological Behavior and NO Degradation Capacity of Asphalt Binder

Abstract: To reduce vehicle exhaust gas pollution in transport-intensive roadways and tunnels, six types of photocatalytic asphalt binders were designed using graphite-phase carbon nitride (g-C3N4) and nanoscale titanium dioxide (nano-TiO2) particles. In this paper, the rheological behaviors and fatigue life of the nano-TiO2-modified asphalt binder (TiO2-MA) and g-C3N4-modified asphalt binder (C3N4-MA) were investigated. NO degradation capacity of six types of photocatalytic asphalt binders was characterized under visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Witkowski et al [28] confirmed the effectiveness of photocatalytic concrete pavements for reducing nitrogen oxide (NO) based on the results of a field study in Warsaw. Wang et al [29] utilized the photocatalyst g-C 3 N 4 and nano-TiO 2 to modify the asphalt binder. The study findings showed that the photocatalyst had a significant ability to degrade NO.…”
Section: Introductionmentioning
confidence: 99%
“…Witkowski et al [28] confirmed the effectiveness of photocatalytic concrete pavements for reducing nitrogen oxide (NO) based on the results of a field study in Warsaw. Wang et al [29] utilized the photocatalyst g-C 3 N 4 and nano-TiO 2 to modify the asphalt binder. The study findings showed that the photocatalyst had a significant ability to degrade NO.…”
Section: Introductionmentioning
confidence: 99%